ORGANIZATIONAL CLIMATE, CAREER DEVELOPMENT AND JOB SATISFACTION TO WORK LOYALTY OF HOUSING OFFICERS ANDSETTLEMENT AREA MALUKU PROVINCE - Muhamad Arsad Rahawarin (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to analyze the effect of organizational climate, career development and job satisfaction partially on job loyalty. The population in this study were all 62 civil servants of the Housing and Settlement Areas of Maluku Province. The sample determination is based on the sample table of Issac and Michael, where at the level of confidence 5%, if the population is 62 people, then the sample is 58 people who are determined by simple random. The analysis used multiple linear regression with the help of SPSS 23.00. The results showed that organizational climate, career development and job satisfaction had a significant effect partially and simultaneously on job loyalty of employees of the Housing and Settlement Service of Maluku Province, where the most dominant variable that had an effect on loyalty was job satisfaction.